How data knowledge transformation affects teachers' precision teaching ability: The mediating effect of data consciousness - Tao, Jia; Fan, Chenchen; Wu, Wenwen; Zhu, Yongyuan (Frontiers in Psychology, 2022)
With the development of smart education, teachers’ precision teaching ability has increasingly become an important component of their professional ability.Based on the Socialization, Externalization, Combination, Internalization (SECI) model of knowledge management, this research constructs a theoretical model of data knowledge transformation, data consciousness, and teachers’ precision teaching ability, and uses Partial Least Squares to analyze the interaction and influence among the elements. The empirical results show that the transformation of internal knowledge related to data has a significant positive impact on the improvement of teachers’ precision teaching ability and data consciousness; the transformation of external knowledge related to teaching has a positive effect on the teaching management ability of teachers’ precision teaching ability, but the effect is not significant. Data consciousness plays a partial mediating effect between internal knowledge transformation and teachers’ precision teaching ability, and a complete mediating effect between external knowledge transformation and teaching management ability.